Permafrost Organic Carbon Turnover and Export Into a High‐Arctic Fjord: A Case Study From Svalbard Using Compound‐specific 14C Analysis - Kusch, Stephanie; Rethemeyer, Janet; Ransby, Daniela; Mollenhauer, Gesine; Rethemeyer, Janet; 3 University of Cologne Institute of Geology and Mineralogy Cologne Germany; Ransby, Daniela; 1 Alfred Wegener Institute for Polar and Marine Research Bremerhaven Germany; Mollenhauer, Gesine; 1 Alfred Wegener Institute for Polar and Marine Research Bremerhaven Germany (Journal of Geophysical Research: Biogeosciences, 2021)
In a warming climate, thawing permafrost soils in the circumpolar Arctic region are subject to enhanced microbial turnover as well as mass mobilization and other erosion processes. High‐Arctic settings such as Svalbard are exceptionally vulnerable to these effects, but the presence of coal deposits obscures the organic carbon (OC) signature of permafrost OC, particularly its carbon isotope composition, when studying OC turnover and export. Here, we analyze the compound‐specific δ13C and Δ14C isotopic composition of alkanoic acids from permafrost soils and river and fjord sediments to assess soil turnover in the catchment of the Bayelva River near Ny‐Ålesund and trace transport and re‐burial of permafrost OC into the adjacent Kongsfjord. Our data confirm the influence of coal‐derived OC on δ13C and Δ14C values of bulk soil and sedimentary OC, while alkanoic acid δ13C and Δ14C values are less affected by coal contributions. Alkanoic acid Δ14C values in the soil profile imply long–term residence in soils prior to deposition in river and fjord sediments, that is, multi‐millennial turnover that is significantly slower than reported from other environments. Strongly 14C‐depleted vascular plant‐derived long‐chain alkanoic acids can be found in Bayelva River and Kongsfjord sediments revealing substantial input of deep active layer/permafrost OC, particularly in the Bayelva River and off its river mouth. In the central Kongsfjord, long‐chain alkanoic acid Δ14C values are higher either reflecting input from other permafrost areas or physical effects resulting, for example, from deposition in settings with different accumulation rates or from sediment sorting. Plain Language Summary: Rising atmospheric temperatures have a particularly strong effect on carbon cycling in high latitude ecosystems such as Svalbard. Thawing of permanently frozen ground (permafrost) results in stronger microbial activity as well as erosion and reburial of previously frozen old carbon‐rich material in aquatic systems. Such processes are poorly ...